Zur Verbreitung und zur Morphologie von Mayetiola destructor (Say, 1817) Kieffer, 1896 (Diptera: Cecidomyiidae). - Stelter, Helmut; Bielka, F.; Rothacker, Dietrich (Contributions to Entomology = Beiträge zur Entomologie, 1991)
A comparison of morphometrical data was made between populations of Mayetiola destructor (Say, 1817) in Kansas (USA) and Gülzow (Mecklenburg). Constant differences in the wing venation (cubitus and position of the branching point) dependent on the origin were established for the two populations. The form of the clawed segments varies considerably in both populations, while the antennae of both sexes show no essential differences.